Induction of Short NFATc1/αA Isoform Interferes with Peripheral B Cell Differentiation - Muhammad, Khalid; Rudolf, Ronald; Pham, Duong Anh Thuy; Klein-Hessling, Stefan; Takata, Katsuyoshi; Matsushita, Nobuko; Ellenrieder, Volker; Kondo, Eisaku; Serfling, Edgar (Frontiers in Immunology, 2018)
In lymphocytes, immune receptor signals induce the rapid nuclear translocation of preformed cytosolic NFAT proteins. Along with co-stimulatory signals, persistent immune receptor signals lead to high levels of NFATc1/αA, a short NFATc1 isoform, in effector lymphocytes. Whereas NFATc1 is not expressed in plasma cells, in germinal centers numerous centrocytic B cells express nuclear NFATc1/αA. When overexpressed in chicken DT40 B cells or murine WEHI 231 B cells, NFATc1/αA suppressed their cell death induced by B cell receptor signals and affected the expression of genes controlling the germinal center reaction and plasma cell formation. Among those is the Prdm1 gene encoding Blimp-1, a key factor of plasma cell formation. By binding to a regulatory DNA element within exon 1 of the Prdm1 gene, NFATc1/αA suppresses Blimp-1 expression. Since expression of a constitutive active version of NFATc1/αA interfered with Prdm1 RNA expression, LPS-mediated differentiation of splenic B cells to plasmablasts in vitro and reduced immunoglobulin production in vivo, one may conclude that NFATc1/αA plays an important role in controlling plasmablast/plasma cell formation.